Assessment of white spot lesions around Orthodontic brackets using different Bonding Agents: an SEM study - Vashishta, Vaibhav; Jaiswal , Raj Kumar; Singh , Amit Kumar; Raj , Stuti; Sehgal , Latika; Srivastava , Nishtha (Journal of Neonatal Surgery, 2025)
Introduction: White spot lesions (WSLs) around orthodontic brackets are a significant concern due to their impact on aesthetics and oral health. This study delves into the factors contributing to WSL formation, exploring their genesis, pathophysiology, and clinical implications. Various factors, such as orthodontic attachment design and archwire ligation, influence WSL development. Remedial approaches and adjunctive treatments aim to prevent or mitigate demineralization during orthodontic intervention. Methods:This study examined WSLs in 10 patients aged 14 to 23 undergoing orthodontic treatment with different bonding composites (AEGIS ORTHO and TRANSBOND XT). Samples were evaluated using scanning electron microscopy (SEM) and image analysis software to quantify WSL severity and lesion depth. Statistical analysis compared the outcomes between the two groups. Results:Both groups experienced increased WSL severity after debonding, with Group A (TRANSBOND XT) showing higher demineralization. Within Group A, demineralization increased significantly after debonding, while Group B (AEGIS ORTHO) remained relatively stable. The net mean change in WSL severity showed 23.0% higher demineralization in Group A. Group B had significantly higher WSL severity and significantly lower lesion depth compared to Group A. Discussion:The study highlights the role of bonding agents in WSL formation and their impact on demineralization. It aligns with previous research on bacterial acids, plaque dynamics, bracket design, and innovative materials like "smart composites." Conclusion:This study underscores the significance of bonding materials in orthodontic treatments and their effects on WSLs. Aegis orthodontic bonding composite with Amorphous Calcium Phosphate (AEGIS ORTHO) exhibited better outcomes in terms of both WSL severity and lesion depth compared to TRANSBOND XT. Further research can build upon these insights to enhance bonding practices and improve the quality of orthodontic interventions.